Audit into stillbirths: a tertiary hospital experience - D’souza, Aparajita Sophia; Gupta, Garima; Masih, Shelesh; Walia, Moneet; Sridhar, Francis K; Goyal, Sunita (International Journal of Research in Medical Sciences, 2017)
Background: The objective of the study was to evaluate the prevalence, risk factors and causes of stillbirth. Methods: A retrospective cohort study was conducted from January 2014 until December 2014 in a tertiary referral teaching hospital in Punjab. The 2014 birth register from the department of Obstetrics and Gynecology was reviewed and the data was collected. The results were tabulated and data was analyzed as frequencies, percentages and descriptive statistics. Results: During the one-year study period, there were 1528 registered pregnancies in the hospital and 64 pregnant women were diagnosed to have stillbirth resulting in a stillbirth rate of 40.63 / 1000 live births. More than 75% of the stillbirths were noted in women between 21 to 30 years of age. Pregnant women who were unbooked (72.5%) had higher rates of stillbirths. More than 80% of the stillbirths were preterm. Anaemia (41.93%), pre-eclampsia (25.8%) and antepartum hemorrhage (24.19%) were the most common maternal risk factors noted in these patients. Maternal factors contributed to 37.5% of the causes of stillbirths. The other causes for stillbirths were placental factors (32.8%) and fetal factors (6.2%). In 23.43% of the cases the cause was unknown. Conclusions: India shares a high burden of stillbirths with priority gaps in reporting and recognizing at the health policy level. Better counting of stillbirths and improved cause-of-death data can advocate child survival strategies.